A panorama of singularities : a panorama of singular varieties conference in celebration of Lê Dũng Tráng's 70th birthday, February 7-10, 2017, University of Seville, IMUS, Seville, Spain - Castro-Jiménez, Francisco-Jesús, 1957-; Massey, David B., 1959-; Teissier, Bernard; Tosun, Meral, 1967- (Contemporary mathematics (American Mathematical Society) ;, 2020)
This volume contains the proceedings of the conference A Panorama on Singular Varieties, celebrating the 70th birthday of Lê Dũng Tráng, held from February 7-10, 2017, at the University of Seville, IMUS, Seville, Spain. The articles cover a wide range of topics in the study of singularities and should be of great value to graduate students and research faculty who have a basic background in the theory of singularities.